Middle ear squamous cell carcinoma: a case report - Mahajan, Nilesh H.; M., Asha; Vijayendra, Vinay Kumar; Honnurappa, Vijayendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Squamous cell carcinoma of middle ear is a rare entity. We present a case of 77 year old male, with squamous cell carcinoma of middle ear. Patient presented with blood tinged otorrhoea. Oto-endoscopy examination revealed a soft tissue lesion in middle ear which bled on touch. Histopathological study of this soft tissue lesion gave a diagnosis of well differentiated squamous cell carcinoma. Radical clearance of the tumour achieved after removal of the malleus and incus. Tumour was seen extending into the eustachian tube orifice and it was removed in toto. Uderlying bone was ablated using diode laser to confirm the radical clearance. Later patient was given radiotherapy 6 weeks after surgery to allow the healing of the operative site. The objective to report this case was to emphasize the importance of early diagnosis and prompt treatment for a better survival. Long standing history of ear discharge with soft tissue lesion bleeding on touch should always be evaluated by histopathological study to exclude malignancy.